Learning Apache Tomcat : from installation to app deployment, monitoring, security, and troubleshooting - Kalin, Martin; Safari eBooks ([Place of publication not identified] : O'Reilly, 2016)
"Tomcat is a web server popular with Java programmers and system admins who need a superior web server to publish their web apps. Written in Java for the Java community, Tomcat is a free production grade web server that is open source, cross-platform (runs on Unix, Linux, Mac OSX, Windows), and very easy to install with no real need for configuration other than for security purposes. System admins love the lightweight Tomcat because it's a no-fuss web server with very reasonable defaults that are easy to customize. In this course, Java and Tomcat wizard Marty Kalin will show you everything you need to know to get Tomcat up and running."--Resource description page.
Presenter, Martin Kalin.
Title from title screen (viewed August 12, 2016).
Date of publication from resource description page.
Keywords: Apache Tomcat; Web servers; Web site development; Internet programming; Electronic books